The Making Research Accessible Initiative: A Case Study in Community Engagement and Collaboration - McCauley, Aleha; Towle, Angela (Partnership, 2022)
Recently community engagement has emerged as a priority among universities, offering new opportunities for their libraries. A literature scan of community-centred work in libraries reveals diverse examples but a lack of conceptual definitions or frameworks to help practitioners advance their work for social impact. We present a case study using the Carnegie Foundation definition of community engagement and apply two conceptual frameworks: living lab constructs and boundary spanning theory. The living lab constructs provide a framework to describe an innovation process that addresses a social challenge, experiments with specific actions for change, and defines specific returns or social impact. Boundary spanning theory provides a framework to help university leaders conceptualize linkages to community in ways that account for institutional complexity and foster reciprocal, mutually beneficial relationships with community partners. We use these two frameworks to describe the Making Research Accessible initiative which has three goals: i) increase the accessibility and impact of research done in the community; ii) increase the availability to researchers of community-generated research; iii) create opportunities for community and university members to share information and learn from each other. From the case study, we summarize what we have learned about community engagement to be of general relevance to library practitioners.